1992
DOI: 10.1111/j.1365-2044.1992.tb01942.x
|View full text |Cite
|
Sign up to set email alerts
|

Colloid solutions in the critically ill

Abstract: SummaryAll patients admitted to an Intensive Care Unit were assigned randomly to one of two groups, A and B. Group A received colloid volume replacement as 4.5% albumin whilst group B received a synthetic colloid, polygeline. This study describes the changes in serum albumin concentration in survivors and nonsurvivors in the two groups during their stay in the Intensive Care Unit. The incidences of renal failure and pulmonary oedema were also assessed. Serum albumin concentration decreased in all nonsurvivors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In more recent studies, investigators have focused on the influence of albumin on duration of ICU stay and rate of recovery. A prospective randomised study of albumin versus gelatin solutions for routine fluid replacement in 475 ICU patients did not show any significant differences between duration of stay, complications or outcomes in the two groups [61]. There are several other studies which failed to show a benefit in using albumin solutions although in all of these studies it was clear that the serum albumin values remained elevated.…”
Section: Correcting Hypoalbuminaemiamentioning
confidence: 99%
“…In more recent studies, investigators have focused on the influence of albumin on duration of ICU stay and rate of recovery. A prospective randomised study of albumin versus gelatin solutions for routine fluid replacement in 475 ICU patients did not show any significant differences between duration of stay, complications or outcomes in the two groups [61]. There are several other studies which failed to show a benefit in using albumin solutions although in all of these studies it was clear that the serum albumin values remained elevated.…”
Section: Correcting Hypoalbuminaemiamentioning
confidence: 99%
“…21 A prospective randomized study of albumin versus gelatin solutions for routine fluid replacement in 475 intensive care unit patients did not show any significant differences between duration of stay, complications or outcomes in the two groups. 22 Unfortunately, albumin treatment appears to increase the relative risk for death in trauma, surgery or burns patients with hypoalbuminemia. 23 In our study, we found that the albumin infusion was associated with shorter survival.…”
Section: Discussionmentioning
confidence: 99%
“…40 A prospective randomized study of albumin versus gelatin solutions for routine fluid replacement in 475 ICU patients did not show any significant differences between duration of stay, complications or outcomes in the two groups. 41 Low serum albumin concentrations are a marker of an underlying disease and not a cause of it. The correction of hypoalbuminemia, so far, has not resulted in a more favorable outcome.…”
Section: Should We Treat a Low Serum Albumin?mentioning
confidence: 99%